2011
DOI: 10.1007/s00216-011-4738-4
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis-mass spectrometry using noncovalently coated capillaries for the analysis of biopharmaceuticals

Abstract: In this work, the usefulness of capillary electrophoresis–electrospray ionization time-of-flight–mass spectrometry for the analysis of biopharmaceuticals was studied. Noncovalently bound capillary coatings consisting of Polybrene-poly(vinyl sulfonic acid) or Polybrene-dextran sulfate-Polybrene were used to minimize protein and peptide adsorption, and achieve good separation efficiencies. The potential of the capillary electrophoresis-mass spectrometry (CE-MS) system to characterize degradation products was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 47 publications
(62 reference statements)
2
72
0
Order By: Relevance
“…The CE-MS analysis was performed using fused-silica capillaries (800 mm × 50 µm I.D., Polymicro Technologies, Phoenix, AZ, USA) coated with a bilayer of Polybrene and poly (vinyl sulfonic acid) as described previously [37]. Sample injections were performed at 1 psi for 12 s. Molecular weight determinations of proteins were performed using the "Charge Deconvolution" utility of the Data Analysis software.…”
Section: Synthesismentioning
confidence: 99%
“…The CE-MS analysis was performed using fused-silica capillaries (800 mm × 50 µm I.D., Polymicro Technologies, Phoenix, AZ, USA) coated with a bilayer of Polybrene and poly (vinyl sulfonic acid) as described previously [37]. Sample injections were performed at 1 psi for 12 s. Molecular weight determinations of proteins were performed using the "Charge Deconvolution" utility of the Data Analysis software.…”
Section: Synthesismentioning
confidence: 99%
“…However, these techniques offer insufficient sensitivity for the detection of PTMs and differentiation of many proteoforms. Studies have shown that even highly pure isolates of a single protein pharmaceutical -recombinant human interferon-β1 (rhINF-β1; Avonex, Biogen) -exist as hundreds of individual proteoforms distributed across a broad dynamic range [1, 25,26]. Such proteoforms may even be combinations of several different PTMs, differentially affecting biological activity [1].…”
Section: Analytical Techniques For Protein Characterizationmentioning
confidence: 99%
“…As a result, comprehensive characterization of a single isolated protein -let alone a complex mixture -is highly challenging, requiring separation prior to high-resolution high mass accuracy MS analysis. We and others have recently demonstrated the power of CZE-MS in high-resolution separations of pharmaceutical glycoproteins [297][298][299]. In our study, a sheathless cross-linked polyethyleneimine-coated capillary coupled to the Orbitrap Elite MS was used to separate proteoforms of recombinant human interferon-β1 (Avonex), resulting in the detection of 138 proteoforms and the separation of deamidated, sialylated, truncated species, and positional glycoform isomers [299].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations